CURRENT SITUATION OF THE HUMAN RESOURCES AT NGUYEN BINH MEDICAL CENTER, CAO BANG PROVINCE (Vietnam Journal of Community Medicine, 2026)
Improving the quality of the health workforce is essential, especially at the grassroots level where human resources are lacking in both quantity and quality. Strengthening the primary healthcare network is a prerequisite for ensuring effective healthcare services for the population. Among these factors, human resources play a decisive role in enabling the Medical Center to fulfill its assigned tasks. Assessing the current situation of the Medical Center’s human resources and identifying solutions to address existing issues are necessary steps to improve the Center’s performance in the coming period. Research method: Cross-sectional descriptive study. The results show that the number of health workers on the payroll of Nguyen Binh Medical Center was 195 in 2023 and 151 in 2024. Doctors accounted for 22.6% in 2023 and 23.2% in 2024, showing a slight upward trend; however, human resource distribution among clinical departments, preventive medicine units, and commune health stations remains uneven. The structure of human resources by professional titles in the clinical sector in 2023 included 19 doctors/32 nurses, technicians, and midwives, corresponding to a ratio of 1 doctor to 1.7 nurses. In 2024, the ratio was 18 doctors/29 nurses, equivalent to 1 doctor to 1.6 nurses, a decrease of 0.1 nurses compared to 2023. In 2023 and 2/18 (1 pharmacist per 9 doctors) in 2024, a decrease of 0.5 pharmacists compared to 2023. In 2023, while in 2024 it was 2/0, showing a reduction of 2 intermediate-level pharmacists compared to 2023. Most staff with postgraduate qualifications are concentrated at the district-level center; meanwhile, commune-level facilities lack highly qualified personnel. The staffing structure per hospital bed does not meet the requirements of Circular 03/2023/TT-BYT. The study proposes strengthening recruitment, training, and adjusting staffing norms to improve the quality of healthcare services for the population.
Keywords: Medical center human resources, medical center sector, commune health stations, health workers.